Dakwah Kultural dalam Animasi Anak: Representasi Islam pada Upin & Ipin dan Nussa - Ahmad Fauzi; Bambang Subahri (Dakwah, 2026)
Children’s animation serves as a strategic medium for conveying Islamic values in a subtle and contextual manner. This article aims to analyze the representation of Islam through clothing and cultural practices in two popular animated series, Upin & Ipin and Nussa. This study employs a qualitative method with a content analysis approach, focusing on selected scenes that depict Muslim attire, Islamic cultural practices, and social interactions among characters. The findings reveal that both animations consistently portray Islam as a friendly, inclusive religion that emphasizes social values such as togetherness, mutual cooperation, modesty, and social care. Muslim clothing is not merely presented as a religious symbol but also as a cultural identity embedded in everyday life. Through simple narratives and visuals that resonate with children, Upin & Ipin and Nussa contribute to shaping a moderate and contextual understanding of Islam from an early age.